2017
DOI: 10.1080/16546628.2017.1344523
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from wheat bran induces cytokine expression via the toll-like receptor 4-mediated p38 MAPK signaling pathway and prevents cyclophosphamide-induced immunosuppression in mice

Abstract: Wheat bran-derived polysaccharides have attracted particular attention due to their immunomodulatory effects. However, the molecular mechanisms underlying their functions are poorly understood. The current study was designed to examine the effect of wheat bran polysaccharide (WBP) on RAW 264.7 cells and the underlying signaling pathways, which have not been explored. In addition, we also investigated the immuno-enhancement effects of WBP on cyclophosphamide (CTX)-induced immunosuppression in mice. WBP signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 53 publications
1
28
2
Order By: Relevance
“…myxogenes activate MAPK and NF-κB pathways and improve immunostimulatory activity in CY-induced imuunosuppressed mice [46]. Polysaccharides of Lonicera japonica , a typical Chinese herbal medicine, and wheat bran-derived polysaccharides markedly promote the serum cytokine levels [47,48], and polysaccharides derived from Stichopus japonicus (sea cucumber), up-regulate the expression of cytokines, such as IL-1β, IL-4, IL-6, IL-10, TNF-α, and IFN-γ, in the CY-induced mice [49]. As CCK-oligosaccharides have an immunostimulating activity, it can be used as an ingredient for functional foods to regulate immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…myxogenes activate MAPK and NF-κB pathways and improve immunostimulatory activity in CY-induced imuunosuppressed mice [46]. Polysaccharides of Lonicera japonica , a typical Chinese herbal medicine, and wheat bran-derived polysaccharides markedly promote the serum cytokine levels [47,48], and polysaccharides derived from Stichopus japonicus (sea cucumber), up-regulate the expression of cytokines, such as IL-1β, IL-4, IL-6, IL-10, TNF-α, and IFN-γ, in the CY-induced mice [49]. As CCK-oligosaccharides have an immunostimulating activity, it can be used as an ingredient for functional foods to regulate immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Because activator protein 1 (AP-1) and MAPK are important downstream signaling molecules that mediate the activation of macrophages and the expression of inflammatory genes, T. Yeo Dae Yoon et al investigated the effect of PG on AP-1 and MAPK activity in the macrophage RAW264.7. The electrophoretic mobility shift assay (EMSA) results showed that PG significantly increases the DNA binding activity of AP-1, and further experiments demonstrated that PG activates three subgroups of MAPK (ERK1/2, SAPK/JNK, and p38 MAPK) (37, 66). When the induction effect of PG was detected after pretreatment of macrophages with specific inhibitors of these three kinases, PG did not show an activation effect, and the DNA binding activity of AP-1 was inhibited by the MAPK inhibitors.…”
Section: Mechanism Of Immunoregulation By Plant Polysaccharidesmentioning
confidence: 99%
“…Some of them are components of the cell walls of plants, such as peptidoglycan and cellulose. Some are nutrients stored in plants and animals, such as glycogen and starch [14]. Scientific experiments show that many polysaccharides have biological activity, including immunomodulatory, antioxidation, antibacterial, and antitumor [15,16].…”
Section: Introductionmentioning
confidence: 99%